18.1k views
1 vote
The slant asymptote for x^3-2x^2+x-4/x^2+1 is y=x-2


True or False?

The slant asymptote for x^3-2x^2+x-4/x^2+1 is y=x-2 True or False?-example-1
User Sency
by
5.8k points

2 Answers

0 votes

Answer:

True. The slant asymptote is
y=x-2

Explanation:

A slant asymptote is the equation of a line of the form y = mx + b

Where m is the slope and b is the cut point with the y axis.

To find these asymptotes, you must make the following limit:


m = \lim_(x \to \infty)(f(x))/(x)


b = \lim_(x \to \infty)[f(x) -mx]

With the given function f(x) we make the first limit to find the slope of the line:


m= \lim_(x \to \infty)((x^3-2x^2+x-4)/(x^2+1))/(x)


m= \lim_(x \to \infty)(x^3-2x^2+x-4)/(x^3+x)

We divide each term between
x ^ 3


m= \lim_(x \to \infty)(1-0 + 0 -0)/(1+0)


m = 1

Now we solve the second limit


b = \lim_(x \to \infty)[(x^3-2x^2+x-4)/(x^2+1)-x]\\\\b = \lim_(x \to \infty)[(x^3-2x^2+x-4 -[x^3+x])/(x^2+1)]\\\\b = \lim_(x \to \infty)[(-2x^2-4)/(x^2+1)]\\\\b = \lim_(x \to \infty)[(-2(x^2)/(x^2)-(4)/(x^2))/((x^2)/(x^2)+(1)/(x^2))]\\\\\\b = -2

Finally: The slant asymptote is
y = x-2

User Ian Timothy
by
5.4k points
6 votes

Answer:

Option 1. T

Explanation:

The given function is f(x)=
(x^(3)-2x^(2)+x-4)/(x^(2)+1)

and the statement states that slant asymptote of the the function is y = x-2

We have to evaluate the statement is true or false.

Now to find the slant asymtote we will divide the numerator by denominator.

We get the function in the form of
f(x)= (x-2)-((2)/(x^(2)+1))

By ignoring the fraction part we can say that the expression which represents the slant asymptote is (x -2).

Therefore the given statement is true.

User Braden Holt
by
5.7k points